The Regulation of Securities Markets in China - He, Weiping (Palgrave Macmillan US, 2018)
This book offers an in-depth analysis of China's contemporary securities markets regulatory system, with a focus on regulation in practice. Examining the roles of both the China Securities Regulatory Commission and local governments, He argues that the government has built and developed markets from scratch to address the needs of the state and the economy at large. This book describes the workings of national and sub-national securities markets, and such a comprehensive approach gives insight into the ability of state regulation to guide a financial system. This book also provides a unique practical perspective, explaining of the dynamics of regulation in relation to the operation of the Chinese political system. Finally, it incorporates original empirical studies, including semi-structured interviews of professionals and a survey of retail investors. This book is an unparalleled resource for anyone interested in the regulation of securities markets, as well as finance in China in general.